How leaders can inspire accountability : three habits that make or break leaders and elevate organizational performance - Timms, Michael (Friesen Press, 2021)
Leadership development consultant Michael Timms has discovered three powerful habits that not only make one a better leader, but also encourage those they lead to take greater accountability themselves. Using a compelling combination of teaching principles and illustrations backed by loads of scientific studies, Timms reveals three habits of personal accountability that are easy to implement and which can instantly begin transforming positional leaders into true leaders who inspire everyone to take more accountability for results.
Keywords: Leadership, Accountability, Organizational Performance